2020
DOI: 10.1177/0003489420903332
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effects on Esophageal Transit Time in the Upright Position During Videofluoroscopy

Abstract: Objectives: The purpose of this study was to examine age-related effects on esophageal transit times (ETT) among healthy adult participants. Methods: A total of 175 healthy, non-dysphagic participants underwent a modified barium swallow study (MBSS), and ETT was recorded for two standardized swallowing tasks. Differences across age groups were determined using Kruskal–Wallis test. Relationships between an Esophageal Clearance (Modified Barium Swallow Impairment Profile Component 17) score and ETT were also exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In the upper intestine, evidence suggests that esophageal motility may be impaired with aging, but data are conflicting and depend on the outcome measured. A recent study in healthy adults ranging in age from 20 to 80 years showed no significant impact of age on total esophageal transit time for thickened foods (eg, nectar and pudding) 23 . Others have also shown no differences in overall transit time, but a recent systematic review and meta-analysis showed the most common age-related changes were a decrease in peristaltic contractility in the distal esophagus as well as a reduction in the relaxation of the lower esophageal sphincter, 24 both of which would seem to contribute to GERD.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the upper intestine, evidence suggests that esophageal motility may be impaired with aging, but data are conflicting and depend on the outcome measured. A recent study in healthy adults ranging in age from 20 to 80 years showed no significant impact of age on total esophageal transit time for thickened foods (eg, nectar and pudding) 23 . Others have also shown no differences in overall transit time, but a recent systematic review and meta-analysis showed the most common age-related changes were a decrease in peristaltic contractility in the distal esophagus as well as a reduction in the relaxation of the lower esophageal sphincter, 24 both of which would seem to contribute to GERD.…”
Section: Introductionmentioning
confidence: 94%
“…A recent study in healthy adults ranging in age from 20 to 80 years showed no significant impact of age on total esophageal transit time for thickened foods (eg, nectar and pudding). 23 Others have also shown no differences in overall transit time, but a recent systematic review and meta-analysis showed the most common age-related changes were a decrease in peristaltic contractility in the distal esophagus as well as a reduction in the relaxation of the lower esophageal sphincter, 24 both of which would seem to contribute to GERD. Gastroesophageal reflux disease is more prevalent in the aging population, with estimates ranging from 15% to 40% of individuals 50 years or older.…”
Section: Gastrointestinal Motility and Transitmentioning
confidence: 99%
“… 27 Uncertainty in the diagnosis of a delayed passage might arise due to the influence of bolus consistency and volume and a normal range of prolonged transport and intra-oesophageal stasis in the ageing population. 28 These cases highlight the need for a comprehensive evaluation of other fluoroscopic pathologies. Adding a tablet of standardized size or a solid bolus test to the examination to assess emptying time increases accuracy.…”
Section: Specific Clinical Questionsmentioning
confidence: 99%